2019
DOI: 10.15244/pjoes/92704
|View full text |Cite
|
Sign up to set email alerts
|

Emission Characteristics for Waste Cooking Oil Biodiesel Blend in a Marine Diesel Propulsion Engine

Abstract: Diesel engines are widely used for propulsion on large ships, which has the undesired characteristic of generating large amounts of harmful emissions. To reduce these emissions, some alternative fuel was developed and used in a marine diesel engine. In this study, an experiment was carried out on a 6-cylinder turbocharged direct-injection marine diesel propulsion engine. A small proportion blend of biodiesel-diesel was used, aimed at exploring the emission characteristics and emission reduction mechanism for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 32 publications
(45 reference statements)
5
21
0
Order By: Relevance
“…Ushakov et al [76] conducted an experiment on a heavy-duty diesel engine with fish oil fuel and reported that total particle concentration and overall PM mass were reduced 67% and 79% respectively. The similar result on the decrease of PM mass and PN when B10 was used in a marine diesel propulsion engine was reported [77]. However, there are reported changes in particle number size distributions i.e.…”
Section: Clean Alternative Fuelssupporting
confidence: 81%
“…Ushakov et al [76] conducted an experiment on a heavy-duty diesel engine with fish oil fuel and reported that total particle concentration and overall PM mass were reduced 67% and 79% respectively. The similar result on the decrease of PM mass and PN when B10 was used in a marine diesel propulsion engine was reported [77]. However, there are reported changes in particle number size distributions i.e.…”
Section: Clean Alternative Fuelssupporting
confidence: 81%
“…Nigeria as a country has made little progress in establishing sustainable energy system amidst many unimplemented policies (Ishola et al, 2019), and her biofuels industry is not an exception (Odetoye et al, 2019). Different types of biofuels emanate from different countries, depending on their available bioresources (Wu et al, 2019), and the technology considered most appropriate and economical (Avagyan and Singh, 2019). Experimentation and continuous research are enabling the development of viable biodiesel feedstocks and suitable production procedures (Abbaszaadeh et al, 2012).…”
Section: Palm Olein As a Sustainable Local Biofuel Feedstock In Nigeriamentioning
confidence: 99%
“…The variation of CO emission with the brake power for the tested fuel blends was compared in Figure . The CO emission is due to incomplete combustion of fuel and depends upon many factors, such as higher viscosity, improper spray pattern, engine temperature, carbon/hydrogen ratio, and air/fuel ratio. , The reduction in CO emission is achieved by enriching the fuel with extra oxygen through increasing the biodiesel percentage, which promotes further oxidation of CO during the exhaust process . CO emission of soapnut biodiesel blends SNB20 and SNB30 was lower at all of the loads compared to diesel.…”
Section: Resultsmentioning
confidence: 99%